The VTA dopaminergic system as diagnostic and therapeutical target for Alzheimer's disease - Krashia, Paraskevi; Spoleti, Elena; D'Amelio, Marcello (Frontiers in Psychiatry, 2022)
Neuropsychiatric symptoms (NPS) occur in nearly all patients with Alzheimer’s Disease (AD). Most frequently they appear since the mild cognitive impairment (MCI) stage preceding clinical AD, and have a prognostic importance. Unfortunately, these symptoms also worsen the daily functioning of patients, increase caregiver stress and accelerate the disease progression from MCI to AD. Apathy and depression are the most common of these NPS, and much attention has been given in recent years to understand the biological mechanisms related to their appearance in AD. Although for many decades these symptoms have been known to be related to abnormalities of the dopaminergic ventral tegmental area (VTA), a direct association between deficits in the VTA and NPS in AD has never been investigated. Fortunately, this scenario is changing since recent studies using preclinical models of AD, and clinical studies in MCI and AD patients demonstrated a number of functional, structural and metabolic alterations affecting the VTA dopaminergic neurons and their mesocorticolimbic targets. These findings appear early, since the MCI stage, and seem to correlate with the appearance of NPS. Here, we provide an overview of the recent evidence directly linking the dopaminergic VTA with NPS in AD and propose a setting in which the precocious identification of dopaminergic deficits can be a helpful biomarker for early diagnosis. In this scenario, treatments of patients with dopaminergic drugs might slow down the disease progression and delay the impairment of daily living activities.